A ecotoxicologia como ferramenta para o monitoramento e perícia ambiental em áreas de mineração - Mariana de Freitas Matos (2019)
The ecotoxicological assessment is a legal instrument of environmental management used in Brazil for surface water quality monitoring, which can provide subsidies for environmental forensic investigation at sites suspected of pollution. Mining activity is a major source of contamination by metals and metalloids that accumulate in the sediment at high concentrations potentially toxic to biota. However, little attention has been given to sediments and soils ecotoxicity, as well as to the importance of using native species in environmental monitoring. In this context, an ecotoxicological assessment of surface water, sediments and soils at sites in the upper course of the São Francisco river basin, was carried out using internationally standardized aquatic bioindicators (Daphnia similis, Ceriodaphnia dubia) as well as representatives of tropical environments (Daphnia laevis, Ceriodaphnia silvestrii, Chironomus xanthus). This study aimed to analyze the current surface water monitoring of Minas Gerais State and subsidize alternatives for environmental monitoring and forensic investigation, with emphasis on mining areas. The results showed acute and chronic toxicity effects of water even at sites where chemical elements were in compliance with legislation. The sediments presented high metals and arsenic concentrations. No acute effects in C. xanthus were observed. However, there was a significant reduction in reproduction of C. dubia and C. silvestrii exposed to sediments as well as acute and chronic toxicity to cladocerans exposed to sediment elutriates. Experiments with soil elutriates demonstrated that they have low retention capacity and can act as contaminants sources. In general, the toxicity effects were higher in the dry season, especially at sites downstream of mining activities. D. laevis was more sensitive than D. similis in sites highly contaminated by metals. C. dubia and C. silvestrii did not present significant differences in reproduction between themselves in surface water and whole sediment samples. However, for elutriates of sediment and soil, there were differences, without a defined pattern among sites and season. In the experiments with the sediment of the gold processing area, avoidance tests with C. xanthus did not show to be a good tool to evaluate sediments contaminated by metals. On the other hand, chronic toxicity was observed, where growth (dry weight) and time of emergency of C. xanthus larvae exposed to sediment samples were significantly delayed compared to controls. It was also found bioaccumulation of metals and arsenic in C. xanthus, as well as in indigenous organisms, demonstrating the impacts of mining activity on a benthic organism. This study showed the importance of including sediment and soil ecotoxicological assessment in environmental monitoring, as well as to consider native organisms in ecotoxicological assays. These assays also showed to be effective in environmental forensic investigation of mining areas.